(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Luthfiyana N, Bija S, Nugraeni CD, Lembang MS, Anwar E, Laksmitawati DR, Nusaibah, Ratrinia PW, Mukmainna. 2022. Characteristics and antibacterial activity of chitosan nanoparticles from mangrove crab shell (Scylla sp.) in Tarakan Waters, North Kalimantan, Indonesia. Biodiversitas 23: 4018-4025. The aim of this study was to determine the characteristics and antibacterial activity of chitosan nanoparticles from mangrove crab shells (Scylla sp.) in Tarakan Waters, North Kalimantan, Indonesia. Chitosan was produced from deproteination, demineralization, and deacetylation processes. Nanoparticles of chitosan were produced by the ionic gelation method. The quality of produced chitosan was tested, and characterized the obtained nanoparticles of chitosan. The results showed that the yield of chitosan was 5.82 ± 0.02%, moisture 1.66 ± 0.05%, ash 1.59 ± 0.21%, nitrogen 1.32 ± 0.06%, and degree of deacetylation (DD) 76 ± 0.00%. All results were in accordance with the Protan Laboratory and Food Safety Authority (EFSA) 2010 standard. Next, the characteristics of chitosan nanoparticles showed that the highest intensity was 15.69 nm, with a polydispersity index of 0.346 and a zeta potential of -26.1 mV. The morphology of chitosan nanoparticles was observed by scanning electron microscopy, energy-dispersive x-ray spectroscopy (SEM-EDX) at 7,500 times magnification. Several elements, such as C and O, were found as constituent elements of chitosan, whereas Mg, Al, P, and Ca, were metal impurities of the shell. Na was derivate from NaTTP, a reactant from mangrove crab nano chitosan. The results of antimicrobial activity revealed that 1% (P4) chitosan extract showed highest zone of inhibition i.e. 13.55 mm and 13.43 mm against Staphylococcus aureus and Staphylococcus epidermidis, respectively.